Oxidative stress specifically inhibits replication of dengue virus. (27th April 2021) - Khan, Naseem Ahmed; Kar, Meenakshi; Panwar, Aleksha; Wangchuk, Jigme; Kumar, Saurabh; Das, Asim; Pandey, Anil Kumar; Lodha, Rakesh; Medigeshi, Guruprasad R.
Abstract : Reactive oxygen species (ROS) are chemically active species which are involved in maintaining cellular and signalling processes at physiological concentrations. Therefore, cellular components that regulate redox balance are likely to play a crucial role in viral life-cycle either as promoters of viral replication or with antiviral functions. Zinc is an essential micronutrient associated with anti-oxidative systems and helps in maintaining a balanced cellular redox state. Here, we show that zinc chelation leads to induction of reactive oxygen species (ROS) in epithelial cells and addition of zinc restores ROS levels to basal state. Addition of ROS (H2 O2 ) inhibited dengue virus (DENV) infection in a dose-dependent manner indicating that oxidative stress has adverse effects on DENV infection. ROS affects early stages of DENV replication as observed by quantitation of positive and negative strand viral RNA. We observed that addition of ROS specifically affected viral titres of positive strand RNA viruses. We further demonstrate that ROS specifically altered SEC31A expression at the ER suggesting a role for SEC31A-mediated pathways in the life-cycle of positive strand RNA viruses and provides an opportunity to identify drug targets regulating oxidative stress responses for antiviral development.